Erasmus Medal Lecture 2019, AE GM Barcelona. Re-imagining the Nation: Memory, Identity and the Emotions. (10th February 2021) - Assmann, Aleida
Abstract : The new nationalism emerging across much of Europe is ready to forgo and forget lessons of history that had successfully domesticated and democratized the nations of the EU over the last 70 years. If the nation, however, is an important resource for integration, and integration is seen as a common project for both its citizens and its migrants, how can it be reimaged and supported to live up to this difficult and important task? This article will analyse these problems in the light of new and older concepts.